Chitosan flocculation associated with biofilms of C. saccharolyticus and C. owensensis enhances biomass retention in a CSTR. (15th June 2021) - Vongkampang, Thitiwut; Rao, Nikhil Seshagiri; Grey, Carl; van Niel, Ed W.J.
Abstract: Cell immobilization and co-culture techniques have gained attention due to its potential to obtain high volumetric hydrogen productivities (QH2 ). Chitosan retained biomass in the fermentation of co-cultures of Caldicellulosiruptor saccharolyticus and C. owensensis efficiently, up to a maximum dilution rate ( D ) of 0.9 h −1 . Without chitosan, wash out of the co-culture occurred earlier, accompanied with approximately 50% drop in QH2 ( D > 0.4 h −1 ). However, butyl rubber did not show as much potential as carrier material; it did neither improve QH2 nor biomass retention in continuous culture. The population dynamics revealed that C. owensensis was the dominant species (95%) in the presence of chitosan, whereas C. saccharolyticus was the predominant (99%) during cultivation without chitosan. In contrast, the co-culture with rubber as carrier maintained the relative population ratios around 1:1. This study highlighted chitosan as an effective potential carrier for immobilization, thereby paving the way for cost – effective hydrogen production. Highlights: Chitosan and biofilm formation could retain biomass during co-culture in a chemostat. The maximum QH2 was 8.4 mmol⋅L −1 ⋅h −1 at a dilution rate ( D ) of 0.8 h −1 . Caldicellulosiruptor species could not utilize chitosan. C. saccharolyticus was the dominant species in the fermentation without chitosan. C. owensensis was the dominant species in the presence of chitosan.